Genome Sequence of Extracellular-Protease-Producing Alishewanella jeotgali Isolated from Traditional Korean Fermented Seafood - Jung, Jaejoon (American Society for Microbiology, 2012)
Alishewanella jeotgali MS1(T) (= KCTC 22429(T) = JCM 15561(T)) was isolated from a traditional Korean fermented seafood, gajami sikhae (jeotgal), and has been reported as a novel species. A. jeotgali was proven to have extracellular proteolytic activity, which may play an important role in the fermentation environment of food containing fish flesh. Here, we present the genome sequence of Alishewanella jeotgali MS1(T) as the first sequenced strain in the genus Alishewanella and its taxonomic relatives.